2018
DOI: 10.4168/aair.2018.10.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Dog and Cat Allergies and Allergen Avoidance Measures in Korean Adult Pet Owners Who Participated in a Pet Exhibition

Abstract: PurposeThis study evaluated dog and cat allergies and their association with allergen avoidance measures in Korean adults.MethodsThe study population consisted of 537 adults who currently kept dogs or cats and participated in a pet exhibition in Korea. The subjects were asked to complete questionnaires regarding pet ownership, allergen avoidance, and allergy symptoms, and underwent skin prick tests. They were considered to have a dog or cat allergy if they suffered from one or more of allergy symptoms during c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…According to a recent study, the most frequent allergic disease entities of cat-allergic patients are rhinitis (80.0%), followed by conjunctivitis (73.3%) and cutaneous symptoms (33.3%). 36 Interestingly, in all tested patients, there was a gender difference between Cat-NPC2-associated allergic disease entities. In fact, striking sex-specific biases have been observed in IgE-mediated allergic diseases such as respiratory allergies, 37 food allergy 38 and anaphylaxis.…”
Section: Discussionmentioning
confidence: 85%
“…According to a recent study, the most frequent allergic disease entities of cat-allergic patients are rhinitis (80.0%), followed by conjunctivitis (73.3%) and cutaneous symptoms (33.3%). 36 Interestingly, in all tested patients, there was a gender difference between Cat-NPC2-associated allergic disease entities. In fact, striking sex-specific biases have been observed in IgE-mediated allergic diseases such as respiratory allergies, 37 food allergy 38 and anaphylaxis.…”
Section: Discussionmentioning
confidence: 85%
“…The most frequent symptoms of cat owners suffering from allergy when exposed to contact with their pets were rhinitis (sneezing, rhinorrhea, nasal obstruction and itching, postnasal drip) (80.0%), followed by conjunctivitis (73.3%), cutaneous symptoms (skin itching, skin rash, angioedema, urticaria) (33.3%), and lower respiratory symptoms (sputum, dyspnea, chest discomfort and pain, wheezing) (13.3%). Dog owners with allergy to their pets suffered from cutaneous symptoms more frequently than cat owners with cat allergy (53.3% vs. 33.3%, P < 0.01), especially in terms of urticaria (35.9% vs. 15.6%, P < 0.01) as well as from lower respiratory symptoms (33.3% vs 13.3%, P < 0.05), especially cough (23.3% vs 6.7%, P < 0.05) [19] .…”
Section: Discussionmentioning
confidence: 98%
“…This is similar to the findings of some previous studies. They have reported that Can f 1 is detected in about one-third of houses that do not own a dog [ 5 8 16 ]. Members of such houses were found to frequently visit a relative who owns a dog, and our findings supported previous results.…”
Section: Discussionmentioning
confidence: 99%
“…Pet ownership in Seoul has increased rapidly, with 20.4% of the population having pets in 2016, and the prevalence of dog ownership among pet owners (88.5%) being remarkably higher than that of cat ownership (26.6%) [ 4 5 ]. Sensitization rates to dogs have not been reported among Korean children, but among adults, they are known to be 7.6% [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation